Visual acuities as measured with an automatic intelligent visual acuity chart projector and standard logarithmic visual acuity chart: a prospective comparative study - Luo, Mingyue; Liu, Xinyu; Zhang, Dingding; Chen, Youxin; Kang, Weijuan (Frontiers in Medicine, 2025)
PurposeThis study aimed to test the repeatability of visual acuity (VA) measurement using an novel intelligent projector visual acuity (IP) chart (LSJ-IVAC-6000A, Hunan Liangshi Jia Biotechnology Co., Ltd.) and the consistency of VA measurement between the IP chart and the 5 m standard logarithmic visual acuity (SL) chart (GB11533-2011).MethodsIn this prospective comparative study, 53 subjects were included to test the internal repeatability of the IP chart. Both eyes of the subjects were tested three times, with a minimum interval of 10 min. The intraclass correlation coefficient (ICC) was used to evaluate the repeatability. One hundred subjects were included to test the consistency between two charts. Both eyes of the subjects were tested with two charts in random order with an interval of 10 min for each test. ICC and the Bland–Altman statistical analyses were used to analyze the consistency of the two charts. VA values were expressed by the logMAR recording method. The time consumption for each test was recorded in seconds.ResultsIn the repeatability analysis, the ICC values of the right and left eye were 0.968 (95% CI, 0.950–0.981, p < 0.001) and 0.964 (95% CI, 0.944–0.978, p < 0.001), respectively. In the consistency analysis, the ICC values of the right and left eye were 0.946 (95% CI, 0.919–0.963, p < 0.001) and 0.817 (95% CI, 0.727–0.877, p < 0.001), respectively. However, the 95% limits of agreement (LoA) of the differences in the VA measurements between the IP and SL chart for the right and left eye were −0.26 to 0.31 and −0.34 to 0.39, respectively, suggesting a certain degree of instability in the measurements of the SL chart. There was no significant difference in the time consumption of VA measurements between the two charts (p = 0.668). In the consistency analysis of subgroups by age, the ICC values were >0.8 (p < 0.001) in the most groups except for the left eyes of 51–70 years old subgroup which had an ICC value of 0.448 (95% CI, −0.919 to 0.841, p = 0.17), with 95% LoA of −1.02 to 0.77.ConclusionThe IP chart demonstrated good repeatability and overall consistency with the SL chart.